Improved measurement of carbonaceous aerosol: evaluation of the sampling artifacts and inter-comparison of the thermal-optical analysis methods - Y. Cheng; KB* He; F.K. Duan; M* Zheng; Y.L. Ma; J.H. Tan; ZY Du (Atmos. Chem. Phys., 2010)
The sampling artifacts (both positive and negative) and the influence of thermal-optical methods (both charring correction method and the peak inert mode temperature) on the split of organic carbon (OC) and elemental carbon (EC) were evaluated in Beijing. The positive sampling artifact constituted 10% and 23% of OC concentration determined by the bare quartz filter during winter and summer, respectively. For summer samples, the adsorbed gaseous organics were found to continuously evolve off the filter during the whole inert mode when analyzed by the IMPROVE-A temperature protocol. This may be due to the oxidation of the adsorbed organics during sampling (reaction artifact) which would increase their thermal stability. The backup quartz approach was evaluated by a denuder-based method for assessing the positive artifact. The quartz-quartz (QBQ) in series method was demonstrated to be reliable, since all of the OC collected by QBQ was from originally gaseous organics. Negative artifact that could be adsorbed by quartz filter was negligible. When the activated carbon impregnated glass fiber (CIG) filter was used as the denuded backup filter, the denuder efficiency for removing gaseous organics that could be adsorbed by the CIG filter was only about 30%. EC values were found to differ by a factor of about two depending on the charring correction method. Influence of the peak inert mode temperature was evaluated based on the summer samples. The EC value was found to continuously decrease with the peak inert mode temperature. Premature evolution of light absorbing carbon began when the peak inert mode temperature was increased from 580 to 650 degrees C; when further increased to 800 degrees C, the OC and EC split frequently occurred in the He mode, and the last OC peak was characterized by the overlapping of two separate peaks. The discrepancy between EC values defined by different temperature protocols was larger for Beijing carbonaceous aerosol compared with North America and Europe, perhaps due to the higher concentration of brown carbon in Beijing aerosol.